Angiotensin ii type 2 receptor agonist, compound 21, prevents tubular epithelial cell damage caused by renal ischemia - Fussi, María Fernanda (2021)
During ischemic acute kidney injury (AKI), loss of cytoskeletal integrity and disruption of intercellular junctions are rapid events in response to ATP depletion. Angiotensin II type 2 receptor (AT2R) is overexpressed in injury situations and its stimulation by angiotensin II (AngII) is related to beneficial renal effects. Its role on ischemic AKI has not been deeply studied. The aim of the present study was to investigate whether pretreatment with the AT2R agonist, C21, prevents ischemic renal epithelial cell injury. Studies in a model of 40 min of renal ischemia followed by 24 h of reperfusion (IR) in rats demonstrated that C21 pretreatment attenuated renal dysfunction and induced better preservation of tubular architecture. In addition, we studied the expression of Rho GTPases, RhoA and Cdc42, since they are key proteins in the regulation of the actin cytoskeleton and the stability of epithelial intercellular junctions. IR downregulated RhoA and Cdc42 abundance in rat kidneys. C21 pretreatment prevented RhoA reduction and increased Cdc42 abundance compared to controls. We also used an in vitro model of ATP depletion in MDCK cells grown on filter support. Using immunofluorescence we observed that in MDCK cells, C21 pretreatment prevented the ATP depletion-induced reduction of actin in brush border microvilli and in stress fibers. Moreover, C21 prevented membrane E-cadherin reduction, and RhoA and Cdc42 downregulation. The present study describes for the first time a renoprotective effect of the AT2R agonist, C21, against AKI, and provides evidence supporting that stimulation of AT2R triggers cytoprotective mechanisms against an ischemic event.